Possible Mechanisms of Chlorpromazine Antihemolytic Effect - Kovalenko, S. E.; Alekseyeva, L. I.; Kuleshova, L. G.; Kovalenko, I. F.; Kholodnyy, V. S.; Gordiyenko, E. O.; Gordiyenko, O. I. (Problems of Cryobiology and Cryomedicine, 2006)
Possible mechanisms of chlorpromazine antihemolytic activity, i.e. changes in erythrocyte membrane surface area and cell potassium outflux, were studied. Cell shape, controlled with MBI-15U light microscope and recorded by a photocamera, was changed by introduction of certain amount of an stomacytogenic cationic amphiphilic substance, chlorpromazine, into the suspension. It was shown, that when increasing the chlorpromasine concentration in erythrocyte suspension with hematocrit of 30% from 0.125 mM up to 1.0 mM the cell shape was changed in the following direction: discocyte®stomatocyte®spherostomatocyte®spherocyte. Potassium ions outflux and erythrocyte distribution on sphericity index were simultaneously determined. The investigations revealed the absence or minor extent of potassium leakage when use the chlorpromazine concentrations, resulting in antihemolytic protection. Therefore, this factor can not be the reason of amphiphilic protection effect against hypotonic hemolysis. Obtained curves of erythrocyte sphericity index distribution density were shown to characterise adequately the spherical rate of cells in the population, and building-in of amphiphilic molecules into erythrocyte membranes in concentrations, being lower as a lytic ones, led to the flattening of part of the cells, i.e. to the rise of their surface area.